Development of soft takraw balls for children - Syafii, M; Karo-Karo, Alan Alfiansyah Putra; Sari, Liliana Puspa; Aditya, Rinaldi; Helmi, Boby; Simangunsong, Benny Aprial (Jurnal Keolahragaan, 2022)
Recognizing and developing the game of sepak takraw at school basic then need to make development according to the level of growth and development of children. This study aims to develop suitable and user-friendly soft takraw balls for children. This research and development adopt the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) which focuses on developing sepak takraw for children's sports by paying attention to three aspects of quality; namely effective, practical, and valid. The takraw balls that were created have been validated by sports experts such as physical education teachers, sepak takraw practitioners, and also by respondents. The results of validation data by experts, a total score of 90% (r=.9) showed high validity. Validation data by media experts and user respondents obtained 100%  (r= 1.0) which is also high validity. It can be concluded that the newly created soft takraw balls for children are suitable for the game nature and user-friendly. The quality of the ball will reduce the cost and increase the usage among young players due to the practicality.